Comprehensive Genomic Analysis of the Endophytic Bacillus altitudinis Strain GLB197, a Potential Biocontrol Agent of Grape Downy Mildew - Zeng, Qingchao; Xie, Jianbo; Li, Yan; Gao, Tantan; Zhang, Xun; Wang, Qi (Frontiers in Genetics, 2021)
Bacillus has been extensively studied for agricultural application as a biocontrol agent. B. altitudinis GLB197, an endophytic bacterium isolated from grape leaves, exhibits distinctive inhibition to grape downy mildew based on unknown mechanisms. To determine the genetic traits involved in the mechanism of biocontrol and host-interaction traits, the genome sequence of GLB197 was obtained and further analyzed. The genome of B. altitudinis GLB197 consisted of one plasmid and a 3,733,835 bp circular chromosome with 41.56% G + C content, containing 3,770 protein-coding genes. Phylogenetic analysis of 17 Bacillus strains using the concatenated 1,226 single-copy core genes divided into different clusters. In addition, average nucleotide identity (ANI) values indicate that the current taxonomy of some B. pumilus group strains is incorrect. Comparative analysis of B. altitudinis GLB197 proteins with other B. altitudinis strains identified 3,157 core genes. Furthermore, we found that the pan-genome of B. altitudinis is open. The genome of B. altitudinis GLB197 contains one nonribosomal peptide synthetase (NRPS) gene cluster which annotated as lichenysin. Interestingly, the cluster in B. altitudinis has two more genes than other Bacillus strains (lgrD and lgrB). The two genes probably obtained via horizontal gene transfer (HGT) during the evolutionary process from Brevibacillus. Taken together, these observations enable the future application of B. altitudinis GLB197 as a biocontrol agent for control of grape downy mildew and promote our understanding of the beneficial interactions between B. altitudinis GLB197 and plants.